Perancangan Aplikasi Media Pembelajaran Pengenalan Pahlawan Nasional untuk Meningkatkan Rasa Nasionalis Berbasis Android - Fithry Tahel; Erwin Ginting (Teknomatika, 2019)
The National Hero is a title given to Indonesian citizens who fought against invaders who died in defense of the nation and state of Indonesia, or produce extraordinary achievements and works for the development and progress of the nation and state of the Republic of Indonesia. This research is motivated by the development of multimedia technology in various fields including in the field of education. The problem is that education in Indonesia still uses many conventional methods, namely by listening to teacher explanations and using books. This method makes students easily bored. Therefore, a learning media is made using interactive multimedia technology based on Android, so students are more enthusiastic about learning. Along with the development of information technology, there are now many devices have been created to facilitate access to information. Information systems about the history of Indonesian Heroes today are still dominated by books. Therefore, researchers will create a learning application for the introduction of national heroes use the development of android-based technology that is growing rapidly nowadays. The purpose of making this learning media is to help students get to know National Heroes in Indonesia to improve memory and nationalist feelings of Tanjung Morawa SDN 104238 students which was developed with Adobe Flash and Android Smartphones.